Assessing the influence of COVID‐19 on the shortwave radiative fluxes over the East Asian Marginal Seas - Ming, Yi; Lin, Pu; Naik, Vaishali; Paulot, Fabien; Horowitz, Larry W.; Ginoux, Paul A.; Ramaswamy, V.; Loeb, Norman G.; Shen, Zhaoyi; Singer, Clare E.; Ward, Ryan X.; Zhang, Zhibo; et al. (AGU Pubication, 2020)
The Coronavirus Disease 2019 (COVID‐19) pandemic led to a widespread reduction in aerosol emissions. Using satellite observations and climate model simulations, we study the underlying mechanisms of the large decreases in solar clear‐sky reflection (3.8 W m⁻² or 7%) and aerosol optical depth (0.16 W m⁻² or 32%) observed over the East Asian Marginal Seas in March 2020. By separating the impacts from meteorology and emissions in the model simulations, we find that about one‐third of the clear‐sky anomalies can be attributed to pandemic‐related emission reductions, and the rest to weather variability and long‐term emission trends. The model is skillful at reproducing the observed interannual variations in solar all‐sky reflection, but no COVID‐19 signal is discerned. The current observational and modeling capabilities will be critical for monitoring, understanding, and predicting the radiative forcing and climate impacts of the ongoing crisis.